Encapsulation of semantic description with syntactic components for the Arabic language - Adel Al-Janabi; Ehsan Ali Kareem; Radhwan Hussein Abdulzhraa Al Sagheer (Institute of Advanced Engineering and Science, 2021)
The work presents new theoretical equipment for the representation of natural languages (NL) in computers. Linguistics: morphology, semantics, and syntax are also presented as components of subtle computer science that form. A structure and an integrated data system. The presented useful theory of language is a new method to learn the language by separating the fields of semantics and syntax.